HUBUNGAN PEMBELAJARAN DARING DENGAN STRES AKADEMIK MAHASISWA MAGISTER FAKULTAS ILMU KOMUNIKASI UNIVERSITAS PADJADJARAN - Muhammad Iqbal Rizaldy; Purwanti Hadisiwi; Pandan Yudhapramesti (EDUTECH, 2022)
The aim of this study is to see if there is a relationship between online learning and academic stress of students of the Masters Program of the Faculty of Communication Sciences, Padjadjaran University. This research is a quantitative study with the population being students of the Masters Program of the Faculty of Communication, Padjadjaran University who are running an online learning process, and the sample is 98 students. The process of collecting data in this study was by distributing online questionnaires using google form. The results of this study are that there is a significant relationship between online learning and work-life balance (H1), then there is a significant relationship between work-life balance and academic stress for Master Program students, Faculty of Communication Sciences, Padjadjaran University (H3), and there is also a relationship between There is a significant relationship between virtual meeting fatigue and academic stress for Master Program students of the Faculty of Communication, Padjadjaran University (H4).